Transgenic Technology and the Study of Hepatitis Viruses: A Review of What We Have Learned - David R Milich (Canadian Journal of Gastroenterology)
Because of the absence of inbred animal models susceptible to infection by the hepatitis B (HBV), C (HCV) and delta (HDV) viruses, and the inability to culture these viruses, a number of investigators have produced transgenic (Tg) mice that express one or all the viral genes. This review attempts to catalogue and characterize the Tg mice produced to date. The topics addressed are HBV, HCV and HDV gene expression and regulation; HBV replication models and factors that inhibit replication; HBV pathogenesis models; HBV tolerance and persistence models; modulation of the immune response to HBV proteins in Tg mice; T cell receptor Tg mice; and models of hepatocellular carcinoma.